A COMPARATIVE STUDY OF EXTROVERTED AND INTROVERTED STUDENTS’ SPEAKING ACHIEVEMENT AT ENGLISH DEPARTMENT OF HALU OLEO UNIVERSITY - Nurzani, Nurzani (Journal of Teaching of English, 2019)
This  study  aimed to  investigate whether there was a  significant difference between extroverted and   introverted students  in   terms of speaking achievement at  speaking I class of English Education Department in   Halu Oleo   University academic  year   2016/2017.  The design   of    this     study   was   quantitative   comparative  study.   The population of  this   study  was the   entire speaking I  class in   English Department  of  Halu  Oleo   University  in   academic  year   2016/2017 which consisted of two  classes in  total of 112 students. The  sample of this    study  was  chosen  randomly  of   all   the    population  by   using Questionnaire  of  Eysenk  Personality  Inventory.  The   instruments  of the  study were questionnaire and   final score of speaking 1  subject. In analyzing the   data  of  the  study,  the  researcher  used  Independent sample   T-test   in    SPSS   16.0     for    windows.   In    this     study,    the Independent  Sample T-test was   showed the   value of  Sig.(2-tailed)  = 0.502  with   α  =  0.05,  H0    was  accepted  and    H1    was   rejected.  It  is because of  sig.   (2-tailed)  value is  higher than α  value. The  result  of this   study  showed that  there  was no   significant difference between extroverted   and     introverted   students’   speaking   achievement   at speaking  I   class  of   English  Education  Department  in    Halu  Oleo University  academic  year   2016/2017.   This study  showed that  the students’ personality,  either  extroverted  or  introverted  did   not   give significant difference on  the  achievement of their speaking Keywords: Extroversion,  Introversion, and   Speaking Achievement